Formare i docenti universitari alla didattica e alla valutazione Temi di approfondimento ed efficacia dei percorsi IRIDI - COGGI, Cristina (Percorsi di ricerca, 2022)
The training of academic faculty in teaching and evaluation has become a mandatory requirement in Europe. This volume aims to propose a review of research about the IRIDI training project carried out at the University of Turin for university professors, in accordance with international contributions and data collected over six years of training. The study allows, on the one hand, for an in-depth examination of the topics involved in the training process and, on the other, for a wide repository of data collected with validated instruments. These offer indications of the effectiveness of the proposed courses and identify factors that differentiate outcomes. In particular are explored the IRIDI FULL course for teaching support dedicated to in-service professors, and the IRIDI START course for researchers, especially newly hired. This paper represents the second research report on the topic proposed in this Series (Coggi, Innovare la didattica e la valutazione in Università, 2019) and is aimed at sharing study outcomes to stimulate further research.